2020
DOI: 10.1186/s12886-019-1275-y
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of the Valsalva maneuver on autonomic nervous system activity, intraocular pressure, Schlemm’s canal, and iridocorneal angle morphology

Abstract: Background: The Valsalva maneuver (VM) is widely used in daily life, and has been reported to cause high intraocular pressure (IOP). This study aimed to assess changes in IOP, the Schlemm's canal (SC), autonomic nervous system activity, and iridocorneal angle morphology in healthy individuals during different phases of the VM. Methods: The high frequency (HF) of heart rate (HR) variability, the ratio of low frequency power (LF) and HF (LF/HF), heart rate (HR), IOP, systolic (SBP) and diastolic blood pressure (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Some investigations have reported a dual effect of the VM on IOP. 18,32 We showed that in some subjects, the SFCT decreased or remained unchanged, while the CVI decreased in some individuals. The large variability in manual measurements of choroidal thickness might explain these discrepancies.…”
Section: Discussionmentioning
confidence: 79%
“…Some investigations have reported a dual effect of the VM on IOP. 18,32 We showed that in some subjects, the SFCT decreased or remained unchanged, while the CVI decreased in some individuals. The large variability in manual measurements of choroidal thickness might explain these discrepancies.…”
Section: Discussionmentioning
confidence: 79%
“…However, other mechanisms have been proposed to explain how the VM increases IOP. One relates to changes in eye muscle activity (45), and another theory involves the autonomic nervous system (58). Although IOP was shown to increase independent of the VM in numerous studies in the present review, it cannot be excluded that the VM was unintentionally performed.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a Valsalva maneuver (VM) compared with unrestricted breathing was shown to significantly elevate blood pressure during RE (39). Furthermore, IOP was increased during a VM alone (58) and accentuated when RE was performed with a VM (65). When lifting heavy loads (>80% maximal voluntary contraction—MVC) and usually as a repetition maximum (RM) is approached, a breath-hold or VM is reflexively performed (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 It has also been suggested that the extraocular muscles play a role in the increase in IOP that is known to occur during lid squeesing. 44 Others Open access have suggested a role for the autonomic nervous system. 42 Sun et al have shown that the expansion and collapse of Schlemms canal during the Valsalva manoeuvre may arise from autonomic nervous system activity as well as the changes in blood flow.…”
Section: Blood Pressure Changesmentioning
confidence: 99%